Tea as a mode of sustainable tourism in Kurseong hill area, Darjeeling, India - DR. RWITABRATA MALLICK,; DR. SWAPNIL RAI, (International Journal of Pharma and Bio Sciences, 2017)
Tea Tourism is the latest concept being popularized in India. The tourists are encouraged to stay in tea garden Bungalows with all amenities. Apart from enjoying serene atmosphere of tea garden they can also see the tea manufacturing process and the unique culture of tea garden. Tea gardens offer nature walks, tea plucking session, trekking, rafting and also golf in some cases. Tea tourism in India is fast catching on popularity with more and more tourists making their way to the lush green tea estates of India. Today, India boasts of three major regions - Assam, Darjeeling and Nilgiris - that produce some of the finest teas in the world. India is the largest producer of tea and contributes around 32% of the total global output. Therefore it is obvious that tea tourism in India is flourishing with the country inviting tourists to observe how its favorite beverage makes its way to people's homes around the world. The objective of the present study is to depict Tea as a mode of Sustainable Tourism and how it can help in sustainable socio-economic development of the study area.